USE OF GREEN MANURE IN GROWING POTATO VARIETIES - Usmanov, Nosir; Hakimova, Mubora (Innovatsion texnologiyalar, 2024)
Under the conditions of old-irrigated typical sierozem soils of the Kashkadarya region, various green manure crops were assessed for the first time in terms of growth, development, yield of green mass and seeds, and promising green manure crops were identified (rapeseed, oilseed radish, peas, blue mustard, peas + oilseed radish). Growth (plant height 71.6-219.6 cm), development (stand density of bushes 103.4-556.2 pcs. per 1 m2) and biomass yield were determined to be 26.4- 34.6 t/ha. It has been studied that an increase in the proportion of macroaggregates by 13.4-25.9% in the arable soil layer, a decrease in microaggregates by 24.7-27.6%, a decrease in volumetric mass by 1.23-1.31 g/cm3, an increase in water permeability by 71 ,0-124.7 m3/ha, increase in humus content by 1.19-1.22%, nitrate nitrogen - 12.38-33.56, available phosphorus - 31.37-43.25, exchangeable potassium - 311, 4-326.2 mg/kg, the degree of weed infestation is 7.4-17.5% or not higher than I and II points, an increase in the number of earthworms by 3.1-6.3 times. The influence of green manure on the growth and development of potato varieties was substantiated (the growing season was extended to 3-10 days, the height was determined to be 66.4-80.7 cm; multi-stem 4.1-5.4 or more than 1.0-1.6 pieces; powerful tops 404.4-495.3 g), formation of productive, healthy ones (tuber yield 617.5-887.5 g, number of tubers - 6.7-11.2, average weight of one tuber - 76.2-90, 3 grams) of bushes and crops, yield (30.7-34.2 t/ha and including marketable yield 29.6-33.4 t/ha, seed tuber yield 21.2-29.2 t/ha, multiplication coefficient in the range of 6.3-8.3) with high seed qualities of various potato varieties.